2018
DOI: 10.1016/j.ajpath.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Negative Breast Cancer, Stem Cells, and African Ancestry

Abstract: Triple-negative breast cancers (TNBCs) are more common among African-ancestry populations, such as African Americans and western, sub-Saharan Africans, compared with European-ancestry populations. This phenotype prevalence contributes to disparities in breast cancer outcomes between African Americans and White Americans. Breast cancer stem cells represent the tumor subpopulation involved in metastatic virulence, and ongoing research seeks to characterize the extent to which TNBC versus non-TNBC stem cells may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 81 publications
(47 reference statements)
2
32
0
1
Order By: Relevance
“…23 The shared genetic ancestry between US-born and Western-Africanborn blacks as a consequence of the historic migration is also supported by evidence from population genetics studies. However, the similarity in breast cancer subtype between US-born and Western-African-born blacks, contrasted against the differences with Eastern-African-born blacks, may in part reflect shared ancestry-related risk factors.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…23 The shared genetic ancestry between US-born and Western-Africanborn blacks as a consequence of the historic migration is also supported by evidence from population genetics studies. However, the similarity in breast cancer subtype between US-born and Western-African-born blacks, contrasted against the differences with Eastern-African-born blacks, may in part reflect shared ancestry-related risk factors.…”
Section: Discussionmentioning
confidence: 88%
“…Most US-born and Caribbean-born blacks are likely descendants of people who were involuntarily migrated from West Africa to North America during the 16th to 18th centuries, often through the Caribbean. 23 The shared genetic ancestry between US-born and Western-Africanborn blacks as a consequence of the historic migration is also supported by evidence from population genetics studies. 11,24 Ancestry analyses among black individuals living in Chicago, Baltimore, Pittsburgh, and North Carolina have shown that ancestry of African Americans is predominantly from Niger-Kordofanian (approximately 71%), the most common ancestry in Western Africa, followed by European (approximately 13%), and other African (approximately 8%) populations.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…TNBC is highly aggressive and associated with poor prognosis. Jiagge et al 6 review epidemiological research that compares socioeconomic status and tumor biology and describe the increased risk for TNBC in women of African descent. They review the genetics and biology of TNBC and discuss how it contributes to the overall disparities in breast cancer outcome.…”
Section: Triple-negative Breast Cancer and African Ancestrymentioning
confidence: 99%
“…The onset of race-group mortality rate disparities coincides with the advent of hormone-targeted therapies [5] that are now standard-of-care for hormone receptor-positive tumors. Compared to women of European descent, AA women [4,[6][7][8][9][10][11][12][13] and women of African descent world-wide [9,[14][15][16] have a higher incidence of triple-negative breast cancer (TNBC) [17][18][19][20][21], which is characterized by the absence of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2). Therefore, in the context of standardizing ER/PR-and HER2-targeted therapies, the divergence of AA vs EA mortality likely unmasked population-level differences in tumor biology, which we have previously shown to correlate with genetic ancestry [22].…”
Section: Introductionmentioning
confidence: 99%